2009
DOI: 10.1897/08-277.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of select organic acids to the slightly thermophilic acidophile Acidithiobacillus caldus

Abstract: Acidithiobacillus caldus is a thermophilic acidophile found in commercial biomining, acid mine drainage systems, and natural environments. Previous work has characterized A. caldus as a chemolithotrophic autotroph capable of utilizing reduced sulfur compounds under aerobic conditions. Organic acids are especially toxic to chemolithotrophs in low-pH environments, where they diffuse more readily into the cell and deprotonate within the cytoplasm. In the present study, the toxic effects of oxaloacetate, pyruvate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Chemoautotrophic bacteria (e.g., Acidithiobacillus and Leptospirillum species) fix inorganic carbon and release excess organic compounds into environments sustaining heterotrophic and mixotrophic prokaryotes (11,70,80). The close interactions between these distinct trophic groups not only facilitate their continued growth but also result in the co-oxidation of minerals (81,82). During the later stages under extremely acidic conditions (pH Ͻ3), the cooperation between autotrophic and heterotrophic species of microbes likely still contributes to the acidification process.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoautotrophic bacteria (e.g., Acidithiobacillus and Leptospirillum species) fix inorganic carbon and release excess organic compounds into environments sustaining heterotrophic and mixotrophic prokaryotes (11,70,80). The close interactions between these distinct trophic groups not only facilitate their continued growth but also result in the co-oxidation of minerals (81,82). During the later stages under extremely acidic conditions (pH Ͻ3), the cooperation between autotrophic and heterotrophic species of microbes likely still contributes to the acidification process.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclopropanation is a modification found commonly in many prokaryotes, especially under stress conditions. Cyclopropanation has been found to increase the acid tolerance of E. coli (Chang and Cronan 2002), and is a common modification found in Acidithiobacillus phospholipids (Cowie et al 2009;Aston et al 2009). Methenylation is found less commonly, and usually in eukaryote-associated organisms such as Mycobacterium ssp.…”
Section: Discussionmentioning
confidence: 99%
“…However, this work is significant because pyruvate has been identified in the spent medium filtrate of At. ferrooxidans (Schnaitman and Lundgren 1965), and is toxic to chemolithotrophic autotrophs at low concentrations under acidic conditions (Aston et al 2009;Matin 1978). In addition, previous work has shown that removing inhibitory organic acids can significantly increase metal-leaching rates (Marchland and Silverstein 2003;Olson et al 2003;Wong 2004, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To test for heterotrophic growth, pyruvate, acetate, citrate, 2-ketoglutarate, succinate, or malate were added to the influent to a sub-lethal concentration of 50 lM (Aston et al 2009). To test for mixotrophic growth, parallel experiments were run, using an influent medium containing 10 mM potassium tetrathionate, in addition to the organic acids, to provide an inorganic electron donor.…”
Section: Media Preparationmentioning
confidence: 99%
See 1 more Smart Citation